The Biology of Brain Metastasis. Issue 4 (July 2015) - Fidler, Isaiah J.
<x xml:space="preserve">Abstract</x> Abstract Many patients with lung cancer, breast cancer, and melanoma develop brain metastases that are resistant to conventional therapy. The median survival for untreated patients is 1 to 2 months, which may be extended to 6 months with surgery, radiotherapy, and chemotherapy. The outcome of metastasis depends on multiple interactions of unique metastatic cells with host homeostatic mechanisms which the tumor cells exploit for their survival and proliferation. The blood-brain barrier is leaky in metastases that are larger than 0.5-mm diameter because of production of vascular endothelial growth factor by metastatic cells. Brain metastases are surrounded and infiltrated by microglia and activated astrocytes. The interaction with astrocytes leads to up-regulation of multiple genes in the metastatic cells, including several survival genes that are responsible for the increased resistance of tumor cells to cytotoxic drugs. These findings substantiate the importance of the "seed and soil" hypothesis and that successful treatment of brain metastases must include targeting of the organ microenvironment.